THE ROLE OF ZAKAT COMMUNITY DEVELOPMENT IN THE ADVANCEMENT OF SMART FARMING TO SUPPORT SUSTAINABLE DEVELOPMENT IN BONDOWOSO REGENCY - Abdul Mu'is; Moch. Chotib; Nikmatul Masruroh (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Islam, as a religion embodying rahmatan lil 'alamin (mercy to all creation), strongly emphasizes the preservation of human welfare, including faith, life, mental health, lineage, and property. This qualitative study, grounded in a post-positivist paradigm and phenomenology, explores the lived experiences of community members involved in smart farming empowerment in Bondowoso Regency. Focusing on the innovative "Subur Berkah" livestock village, data were collected through participant observation, semi-structured interviews with Baznas representatives and locals, and documentation. Snowball sampling identified informants with rich experiential knowledge. The researcher acted as the primary instrument, ensuring authentic engagement and data collection. Data analysis employed the interactive model of Miles, Huberman, and Saldana, involving condensation, display, and iterative conclusion drawing. Findings reveal that Baznas transforms zakat from charity into productive empowerment by identifying beneficiaries, delivering intensive training, and maintaining ongoing support, fostering economic and social independence. Smart farming innovations such as integrated housing, fermented feed, data-driven health management, and digital tools enhance livestock productivity and income. This participatory empowerment model significantly advances sustainable development goals by addressing poverty, food security, employment, inequality, and promoting environmentally sustainable, technology-driven rural development.